The Fourier analysis of picosecond acoustic signals generated by laser beam in Au/V nanolayers - Aleksiejuk, M.; Rejmund, Feliks (Archives of Acoustics, 2006)
Paper presents the results of study of picosecond acoustic signals generated by femtosecond laser pump pulse in Au/V multilayers. Au/V nanostructures with a period of 36-205Å located on MgO substrate were studied. The dependence of measured changes of the laser light reflectivity from nanostructure surface on different delays of probe beam was examined. Peak frequencies obtained by FFT analysis were interpreted as frequencies of acoustical localized modes. The obtained values of these localized modes are in agreement with numerical results. In the same sample localized modes were excited simultaneously in the first and second frequency forbidden gaps.